Immediate Beneficial Effects of Mental Rotation Using Foot Stimuli on Upright Postural Stability in Healthy Participants. (26th December 2013) - Kawasaki, Tsubasa; Higuchi, Takahiro
Abstract : The present study was designed to investigate whether an intervention during which participants were involved in mental rotation (MR) of a foot stimulus would have immediate beneficial effects on postural stability (Experiment 1) and to confirm whether it was the involvement of MR of the foot, rather than simply viewing foot stimuli, that could improve postural stability (Experiment 2). Two different groups of participants (n = 16 in each group) performed MR intervention of foot stimuli in each of the two experiments. Pre- and postmeasurements of postural stability during unipedal and bipedal standing were made using a force plate for the intervention. Consistently, postural sway values for unipedal standing, but not for bipedal standing, were decreased immediately after the MR intervention using the foot stimuli. Such beneficial effects were not observed after the MR intervention using car stimuli (Experiment 1) or when participants observed the same foot stimuli during a simple reaction task (Experiment 2). These findings suggest that the MR intervention using the foot stimuli could contribute to improving postural stability, at least when it was measured immediately after the intervention, under a challenging standing condition (i.e., unipedal standing).